2011
DOI: 10.1038/cmi.2011.28
|View full text |Cite
|
Sign up to set email alerts
|

CDR3δ -grafted γ9δ2T cells mediate effective antitumor reactivity

Abstract: Adoptive cell-transfer therapy (ACT) has been reported to suppress growing tumors and to overcome tumor escape in animal models. As a candidate ACT effector, c9d2T cells can be activated and expanded in vitro and in vivo and display strong antitumor activity against colorectal, lung, prostate, ovarian and renal cell carcinomas. However, it is difficult to obtain a large enough number of cdT cells to meet the need for immunotherapy that can overcome the cancer patients' immune suppressive tumor microenvironment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 37 publications
(42 reference statements)
0
12
0
Order By: Relevance
“…Ectopically expressed hMSH2 in a malignant environment, including virus infection, oxidative stress, and tumorigenesis, created a signal alerting the immune system in immunosurveillance via ␥␦ T cells (14,15). Further, engineered antibodies, based on the CDR3␦ sequence, showed tumor binding specificity and antitumor effects in mouse xenograft models (19,20). In this study, we demonstrated that a novel autoimmune disease-associated antigen CCT6A is recognized by ␥␦ T cells.…”
Section: Discussionmentioning
confidence: 74%
“…Ectopically expressed hMSH2 in a malignant environment, including virus infection, oxidative stress, and tumorigenesis, created a signal alerting the immune system in immunosurveillance via ␥␦ T cells (14,15). Further, engineered antibodies, based on the CDR3␦ sequence, showed tumor binding specificity and antitumor effects in mouse xenograft models (19,20). In this study, we demonstrated that a novel autoimmune disease-associated antigen CCT6A is recognized by ␥␦ T cells.…”
Section: Discussionmentioning
confidence: 74%
“…Although they represent only a small population of immune cells, cd-T cells exhibit features characteristic of both innate and adaptive immunity and play an indispensable role in host defense, immune surveillance and homeostasis. [1][2][3][4] In humans, cd-T cells constitute approximately 1%-5% of circulating T cells, and most of them bear the Vc9Vd2 T-cell receptor (TCR). 5,6 Human Vc9Vd2-T cells can be specifically activated in an HLA-unrestricted manner by small non-peptidic phosphoantigens, which are metabolites of the isoprenoid biosynthesis pathways.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Vc9Vd2-T cells are the major cd-T-cell population in peripheral blood in humans, and these cells exhibit characteristics of both innate and adaptive immune responses. [9][10][11] It has been shown that human Vc9Vd2-T cells have antiviral activity against different viruses, including influenza virus, through cytolytic and non-cytolytic mechanisms. [12][13][14][15] Vc9Vd2-T cells can directly kill influenza virus-infected cells through the release of perforin and granzyme B.…”
Section: Introductionmentioning
confidence: 99%